Proposals for Second Five Year Plan Road Transport Sector Government of Rajasthan - Planning Commission (Planning Commission, 1955)
In view of the fact that Rail haulage is comparatively low in Rajasthan, a very great proportion of the burden of the expanding economy in every sector of the Plan will have to be borne by the Road Transportation system in Rajasthan.
Government of Rajasthan, Planning Department